Modeling and Mapping Personal Learning Environment of Thai International Higher Education Students - Sharafuddin, Mohamed Ali; Sawad, Buncha Panacharoen; Wongwai, Sarun (Asian Journal of Education and Training, 2018)
This research article is part of a periodic study conducted to understand, model, map and to develop an integrated approach for effective and interactive self-learning phases of Thai International Hospitality and Tourism higher education students. Questionnaire containing both qualitative and quantitative questions was distributed at the beginning of the semester to understand the students’ personal learning environment during their self-learning phases. After obtaining mutual agreement with the students, the researcher diffused the course related contents and assignments through observed personal learning environment and the changes that took place in it. Thereafter, the students’ learning experience was measured again by the end of the semester with another quantitative questionnaire. Paired sample t-test and regression analysis were conducted to analyze the outcomes. The results revealed that there was statistically significant difference between the past and the present self-learning phases of personal learning environment on using micro blogging, academic material search engines, group chats, collaborative office suites (Social Networking Tools), Microsoft office suite and other traditional methods such as using teaching learning resources and infrastructure provided by institution (books, handouts, lecture notes and university library). The multiple linear regression results revealed that, the above mentioned self-learning phases of PLE attributes has significant and positive impact on overall learning experience.